Immigration policy in the age of punishment: detention, deportation, and border control - Brotherton, David; Kretsedemas, Philip (Studies in transgression, 2017)
Introduction : immigration policy in an age of punishment / Philip Kretsedemas and David Brotherton -- Obama's legacy as "deporter in chief" / Tanya Bolash-Goza -- Immigration policy and migrant support organizations in an era of austerity and hope / Deirdre Conlon -- Ordinary injustices : persecution, punishment, and the criminalization of asylum in Canada / Graham Hudson -- Seeking asylum in Australia : the role of emotion and narrative in state and civil society responses / Greg Martin and Claudia Tazreiter -- Critiquing zones of exception : actor-oriented approaches explaining the rise of immigration detention / Matthew B. Flynn and Michael Flynn -- The controlled expansion of local immigration laws : an analysis of US Supreme Court jurisprudence / Philip Kretsedemas -- The sociology of vindictiveness and the deportable alien / David C. Brotherton and Sarah Tosh -- Banished yet un-deported : the constitution of a 'floating population' of deportees within France / Carolina Boe -- Fear of deportation as a barrier to immigrant integration / Shirley Leyro -- Deported to Tijuana : social networks and religious communities / Maria Dolores Paris and Gabriel Perez Duperou -- Medical deportations : blurring the line between health care and immigration enforcement / Lisa Sun-Hee Park -- Citizenship in the green card army / Sofya Aptekar -- The production of immigration exclusions under H-1B and l-1 visas / Payal Banerjee -- The precarious deportee and human rights in the Dominican Republic / Yolanda Martin